Environmental Remediation with Functional Aerogels and Xerogels. Issue 10 (17th June 2020) - Riley, Brian J.; Chong, Saehwa
Abstract: Several different types of aerogels and xerogels are demonstrated as effective sorbents for the capture and/or immobilization of radionuclides and other contaminants in gaseous form [e.g., Hg(g), I2(g), Xe, Kr] as well as ionic form (e.g., Cd 2+, Ce 4+, Cs +, Cu 2+, Fe 2+, Hg 2+, I −, IO3 −, Kr, Pb 2+, Rb +, Sr 2+, 99 Tc 7+, U 6+, Zn 2+ ). These sorbents have unique properties, which include high specific surface areas, high pore volumes, a range of pore sizes, and functionalities that provide methods for binding radionuclides and other contaminants, generally through physisorption, chemisorption, or a combination thereof. This combination of properties and functionalities makes these types of materials ideal for use as sorbents for capturing radionuclides. The primary base materials that will be discussed in this paper include Ag 0 ‐functionalized silica aerogels, Ag + ‐impregnated aluminosilicate aerogels, Ag 0 ‐functionalized aluminosilicate aerogels, metal‐impregnated (non‐Ag) aluminosilicate aerogels and xerogels, sulfide‐based aerogels, and carbon‐based aerogel composites. For the capture of I2(g), the materials reported herein show some of the highest iodine loadings ever reported for inorganic sorbents. For the capture of ionic species, these materials also show promise as next‐generation materials for active radionuclide remediation. This progress report describes materials fabrication, general properties, and environmental remediation applications. Abstract : Functionalized aerogels and xerogels are demonstrated for use in the removal of contaminants from aqueous and gaseous streams, including species such as halides, noble gases, actinides, lanthanides, alkalis, and alkaline earths that could pose environmental and health concerns if not captured and contained properly. This paper provides a progress report of the current state of the art in this area.